Strong Electrorheological Performance of Smart Fluids Based on TiO2 Particles at Relatively Low Electric Field - Cheng, Yuchuan; Zhao, Zihui; Wang, Hui; Hua, Letian; Sun, Aihua; Wang, Jun; Li, Zhixiang; Guo, Jianjun; Xu, Gaojie (Frontiers in Materials, 2021)
Electrorheological (ER) fluids are a type of smart material with adjustable rheological properties. Generally, the high yield stress (>100 kPa) requires high electric field strength (> 4 kV/mm). Herein, the TiO2 nanoparticles were synthesized via the sol-gel method. Interestingly, the ER fluids based TiO2 nanoparticles give superior-high yield stress of 144.0 kPa at only 2.5 kV/mm. By exploring the characteristic structure and dielectric property of TiO2 nanoparticles and ER fluid, the surface polar molecules on samples were assumed to play a crucial role for their giant electrorheological effect, while interfacial polarization was assumed to be dominated and induces large yield stress at the low electric field, which gives the advantage in low power consumption, sufficient shear stress, low leaking current, and security.